Ultrastructures of Epibiotic Suctorian, Tokophrya huangmeiensis - Tahir, Urfa Bin; Qiong, Deng; Zhe, Wang; Sen, Li; Yang, Liu; Zemao, Gu (Zootaxa, 2018)
Tokophrya species are either free-living or facultative ectosymbiotic suctorians associated with copepods, isopods, mysids, decapods and amphipods. Tokophrya huangmeiensis in particular is found to be epizoic with the redclaw crayfish Cherax quadricarinatus Von Martens, 1868, which has been observed as part of an ongoing investigation of freshwater ciliates biodiversity in Huanggang, Hubei, China (Tahir et al. 2017). This first study on T. huangmeiensis based on morphological features using light microscopy and small subunit ribosomal DNA sequence (Tahir et al. 2017), suggested that more detailed descriptions on the physiological and structural changes of this species should be done. Thus, in this study, we looked at the ultrastructures of T. huangmeiensis using electron microscopy, including both scanning (SEM) and transmission electron microscopy (TEM).